(untitled) - Lewis, Alan (Boston, Massachusetts, 2016)
In today’s volatile economic environment, filled with uncertainty and sudden change, the forces pushing you to stay focused on the core business are extremely powerful. Profiting from the core is crucial, but the danger is that overfocus on the core can blind companies. Scanning the horizon for new markets and new products can also be tempting, but risky. Fixating too much on either strategy can cause you to miss the substantial opportunities for growth that are often hidden in plain sight, at the edge of the core business.
Keywords: Kế hoạch chiến lược,Strategic planning